2014
DOI: 10.3389/fnins.2014.00284
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cross-frequency coupling in the tinnitus network

Abstract: Neuroimaging studies have identified networks of brain areas and oscillations associated with tinnitus perception. However, how these regions relate to perceptual characteristics of tinnitus, and how oscillations in various frequency bands are associated with communications within the tinnitus network is still incompletely understood. Recent evidence suggests that apart from changes of the tinnitus severity the changes of tinnitus dominant pitch also have modulating effect on the underlying neuronal activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 86 publications
3
35
0
Order By: Relevance
“…Indeed, CFC has been proposed to be an effective mechanism in combining network activity with sensory processing (44)(45)(46). Significantly different CFC patterns between low-frequency rhythms and gamma rhythm were found within the S1 cortex following IoN ligations in WT, compared with KO mice (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, CFC has been proposed to be an effective mechanism in combining network activity with sensory processing (44)(45)(46). Significantly different CFC patterns between low-frequency rhythms and gamma rhythm were found within the S1 cortex following IoN ligations in WT, compared with KO mice (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Approximately 2% of the general population experience a severely impaired quality of life due to this condition and rely on professional medical, psychological, or psychiatric help (Axelsson and Ringdahl, 1989;Langguth, 2012). Although many theories have been proposed concerning the etiology, the neuronal fingerprint of primary tinnitus is the altered spectral power of electroencephalography (EEG) or magnetoencephalography signals (Weisz et al, 2005;Dohrmann et al, 2007;Kahlbrock and Weisz, 2008;Ortmann et al, 2011;Adamchic, Langguth, et al, 2014;Adamchic, Toth, et al, 2014;Eggermont and Tass, 2015) observable over a large network of brain areas (Schlee et al, 2008;2009;Silchenko et al, 2013;Sedley et al, 2015) A number of distinct therapeutic options have been proposed for the management of primary tinnitus (Tunkel et al, 2014) including cognitive behavioral therapy (Martinez-Devesa et al, 2010), hearing aids (Hoare et al, 2014), cochlear implants (Arts et al, 2015), sound maskers (Hobson et al, 2012), tinnitus retraining therapy (Phillips and McFerran, 2010), medications (Hoekstra et al, 2011;Baldo et al, 2012;Hilton et al, 2013), vitamins and dietary supplements, hyperbaric oxygen (Bennett et al, 2012), acupuncture (Kim et al, 2012), and neuromodulation therapy (Langguth and De Ridder, 2013). Currently, there is no standard of care and the published studies have large variability in outcomes and large differences in intervention protocols within a single type of intervention.…”
mentioning
confidence: 99%
“…Owing to the centrality of feeder nodes, damage/intervention to these sites results in dynamic changes in the connectivity profile of the module resulting in the disconnection of the communities from the core. Further, it has been shown that there exists an aberrant cross-frequency coupling in tinnitus between different regions in the brain (Adamchic, Langguth, Hauptmann, & Tass, 2014;. This…”
Section: Accepted Manuscriptmentioning
confidence: 94%